Pulmonary Function of Young Muslim Males During the Month of Ramadan - Singha Roy, Anindita (Am J Mens Health, 2016)
During the month of Ramadan intermittent fasting (RIF), both dietary and sleep patterns are adversely affected to cope with the rituals of Ramadan. Literature suggests that sleep deprivation and alteration of dietary pattern and nutritional impairment affect the pulmonary structure and function. Pulmonary function during RIF was not explored earlier. The present study aimed to investigate the effects of RIF on pulmonary function tests (PFTs) in healthy young Muslim males. Fifty sedentary nonsmoking healthy young Muslim male individuals of 20 to 25 years of age without any history of pulmonary or other major diseases were recruited by simple random sampling from different parts of Kolkata, India. Participants completed the American Thoracic Society questionnaire to record their personal demographic data, health status, and consent to participate in the study. Expirograph and peak flow meter were used to record the pulmonary function parameters (PFTs). PFTs were within the normal range and did not show any significant variation during the RIF. Body height and body mass depicted significant correlation (p < .05, p < .001) with PFTs. Tidal volume, vital capacity, and peak expiratory flow rate had significant correlation (p < .05, p < .01, p < .001) with age. Simple and multiple regression equations were computed to predict PFTs in the studies population. RIF did not affect the normal range of PFTs in young Muslim males of Kolkata, India. Standard errors of estimate of the computed regression equations were substantially small enough to recommend these equations as norms to predict the PFTs in the studied population.